Autoimmune Pancreatitis Type 2: Case Report. (October 2017) - Onweni, Chidinma; Balagoni, Harika; Treece, Jennifer M.; Addo Yobo, Emmanuel; Patel, Archi; Phemister, Jennifer; Srinath, Manoj; Young, Mark F.
A middle-aged man presents with acute pancreatitis of unknown etiology and is found to have a presentation consistent with the diagnosis of type 2 autoimmune pancreatitis (AIP). AIP is a group of rare heterogeneous diseases that are challenging to diagnose. There are 2 types of AIP. Type 1 disease is the more common worldwide than type 2 AIP. While type 1 AIP is associated with IgG4-positive antibodies, type 2 AIP is IgG4 antibody negative. Both types of AIP are responsive to corticosteroid treatment. Although type 1 AIP has more extrapancreatic manifestations and more commonly relapses, this is a case of a patient with type 2 AIP with inflammatory bowel disease and relapsing course.